Factores socioculturales en las experiencias sexuales en adolescentes. - Guijarro Rosero, Alisson Pamela (2025)
Sociocultural factors include the conditions of the family, educational, religious, and social environment that influence adolescents' behavior and decision-making, while sexual experiences encompass the initiation and development of sexual practices at this stage. The objective of the study was to analyze the influence of sociocultural factors on sexual experiences and risky behaviors in adolescents through a literature review. The research is a systematic review of a descriptive level and bibliographic type, based on the analysis of information from scientific articles, theses, books, and documents issued by international organizations. The study population is determined by 1073 scientific documents and a sample of 21 evaluated scientific articles, using a methodological quality matrix, Critical Review Form-Quantitative Studies (CRF-QS). Simultaneously, the PRISMA methodology was used to organize and analyze the information gathered from scientific studies. The results showed that factors such as parenting style, lack of communication with parents, scant parental supervision, low educational attainment, peer pressure, substance use, the influence of restrictive religious beliefs, and exposure to sexual content on social media are directly related to early onset of sexual activity, unprotected sex, unplanned pregnancies, and sexually transmitted infections. As a consequence of these practices, there are significant impacts on the lives of adolescents, such as family conflicts, adverse emotional and psychological effects, physical health risks, economic risks, school dropout, poor academic performance, as well as limitations in their personal development and life plans. In conclusion, the relationship between sociocultural factors, sexual experiences, and risk behaviors in adolescents is important; this demonstrates the need to promote family, educational, and clinical interventions focused on the prevention of risky sexual behavior through comprehensive sex education, strengthening family relationships, and access to emotional support programs.